Immunotherapy for the treatment of multiple myeloma - Boussi, Leora S.; Avigan, Zachary M.; Rosenblatt, Jacalyn (Frontiers in Immunology, 2022)
Despite advances in treatment for multiple myeloma, the majority of patients ultimately develop relapsed disease marked by immune evasion and resistance to standard therapy. Immunotherapy has emerged as a powerful tool for tumor-directed cytotoxicity with the unique potential to induce immune memory to reduce the risk of relapse. Understanding the specific mechanisms of immune dysregulation and dysfunction in advanced myeloma is critical to the development of further therapies that produce a durable response. Adoptive cellular therapy, most strikingly CAR T cell therapy, has demonstrated dramatic responses in the setting of refractory disease. Understanding the factors that contribute to immune evasion and the mechanisms of response and resistance to therapy will be critical to developing the next generation of adoptive cellular therapies, informing novel combination therapy, and determining the optimal time to incorporate immune therapy in the treatment of myeloma.